Evaluasi Pemberlakuan Hak yang Tidak Didapat Narapidana Seumur Hidup pada Lapas Kelas I Surabaya - Rofi Triatmaja, Yahya; Subroto, Mitro (Jurnal Syntax Fusion, 2021)
Each type of violation has its own term of punishment. For crimes such as theft and robbery, it ranges from 5 – 10 years in prison. However, it is different with the act of drug abuse and murder which gets a life sentence. For those who are still laymen, life imprisonment means that the convict spends the rest of his life in a correctional institution. But in reality it is not so. Life sentences range from 20-25 years. The research method used is descriptive qualitative. In this approach, the research procedure produces descriptive data in the form of written or spoken words from the observed people and observed behavior. The qualitative approach is carried out in natural conditions and is discovery. In a qualitative approach, the researcher is the main instrument. This approach is used to review the quality of the implementation of rights that are not obtained by life inmates in Class I prisons in Surabaya, the results are then described in detail. Data collection techniques used were interviews to obtain information on the implementation of rights that were not obtained by lifelong prisoners and documentation to obtain references. The results of this study are in the form of an explanation of the implementation of rights that are not obtained by lifelong prisoners at the Class I prison in Surabaya.